Information consistency as response to pre-launch advertising communications: The case of YouTube trailers - Kampani, Julia; Nicolaides, Christos (Frontiers in Communication, 2023)
Pre-launch advertising communications are critical for the early adoption of experiential products. Often, companies release a variety of advertising messages for the same product, which results in a lack of information consistency. Research on the effect of advertising communications with different message content is scarce. Further, most studies on information consistency rely on experimental methods, leaving the actual effect of consumer response on product adoption unknown. Treating online comments to movie trailers as consumer response to advertising communication, we propose a natural language processing methodology to measure information consistency. We validate our measurement through an online experiment and test it on 1.3 million YouTube comments. Our empirical results provide evidence that information consistency driven by trailer-viewing is a key driver of opening box office success. Insights deriving from this study are important to marketing communications research, especially in contexts where early product adoption is critical.